Pengembangan Sistem Pelaporan Hazard Dan Manajemen Risiko Keselamatan Berbasis Web Pada Bandar Udara - Triyani Retno Putri Sari Dewi (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
Hazard reporting is very important in aviation safety management system. Hazards identified through the report can be used to manage safety risks. With advances in technology, hazards can be reported online more quickly so that mitigation can be carried out immediately. This study aims to develop a web-based hazard reporting and safety risk management system to improve the reporting culture at airports and manage safety risks in a more effective manner. This study uses a design-based research method with four stages, namely problem analysis, solution development, product testing and improvement, and reflection. The results of user acceptance test show that the design is effective and useful for reporting hazards and managing safety risks.